EFEKTIVITAS PENDIDIKAN KESEHATAN BANTUAN HIDUP DASAR TERHADAP PENGETAHUAN KADER DASAWISMA - tiara tiara; Sudarti Sudarti; Maghfira Anggreini; Nadia Novitasari; Insani Tiara Tirta; Hestika Ardianty; Nur Rahmadhaniah; Nurcahyani Putri Rahmadani; Nur Aisyah; Maajid Surya Putra Ashari; Bachtiar Safrudin; Lenny Retnawati (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2025)
Cardiac arrest is a medical emergency that requires a quick response from first responders to increase the chances of survival. Dasawisma cadres, as part of the community, play an important role in providing first aid, so it is necessary to increase their knowledge through structured health education. This study aims to determine the effectiveness of health education on Basic Life Support in improving the knowledge of Dasawisma cadres. The research method used an intervention design with a sample of 14 Dasawisma cadres in Air Putih Village, Samarinda Ulu District who participated in a series of health education activities in the form of lectures, interactive discussions, demonstrations, and hands-on practice with teaching aids. Data were collected through pretest and posttest instruments to assess changes in the knowledge of Dasawisma cadres. The results showed a significant increase in the knowledge category from 35.7% before the intervention to 92.9% after the training. This increase indicates that the health education provided was able to improve the cadres' understanding of cardiac arrest recognition and the correct implementation of chest compressions. These findings prove that educational activities accompanied by direct demonstrations are effective in improving cadres' preparedness in handling emergencies. In conclusion, basic life support health education has been proven to significantly improve cadres' knowledge. It is recommended that similar training be conducted periodically and supplemented with practical evaluations so that cadres' skills are maintained and can be applied when emergencies occur in the community.